2012
DOI: 10.1128/jvi.01862-12
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Evolutionary Pressures Underlie Diversity in Simian Immunodeficiency Virus and Human Immunodeficiency Virus Lineages

Abstract: iSimian immunodeficiency virus (SIV) infection of rhesus macaques causes immune depletion and disease closely resembling human AIDS and is well recognized as the most relevant animal model for the human disease. Experimental investigations of viral pathogenesis and vaccine protection primarily involve a limited set of related viruses originating in sooty mangabeys (SIVsmm). The diversity of human immunodeficiency virus type 1 (HIV-1) has evolved in humans in about a century; in contrast, SIV isolates used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 92 publications
3
40
0
Order By: Relevance
“…In terms of vulnerability to neutralizing antibodies, most of the SIVsm Envs in the panel seemed to behave more similarly to HIV-1 than HIV-2 Envs. The driving force for masking of conserved epitopes during natural infection with SIVsm is not immediately clear, given evidence of lower diversifying selection in Env gp120 (101) and lower autologous neutralizing antibody titers in naturally infected sooty mangabeys (39) than individuals infected with HIV-1. Unfortunately, the determinants of neutralization pan-resistance in some of the tier 3 SIVsm Envs or the identification of reagents that neutralize them will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of vulnerability to neutralizing antibodies, most of the SIVsm Envs in the panel seemed to behave more similarly to HIV-1 than HIV-2 Envs. The driving force for masking of conserved epitopes during natural infection with SIVsm is not immediately clear, given evidence of lower diversifying selection in Env gp120 (101) and lower autologous neutralizing antibody titers in naturally infected sooty mangabeys (39) than individuals infected with HIV-1. Unfortunately, the determinants of neutralization pan-resistance in some of the tier 3 SIVsm Envs or the identification of reagents that neutralize them will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies demonstrated the potential of centralized and polyvalent vaccines to enhance the immune coverage of diverse HIV-1 strains by expanding the breadth and the depth of cellular immune responses. In contrast to HIV mosaics conferring protection in an SHIV challenge model, SIV mosaic Env designs based on a small set of available sooty mangabey natural SIV variants (30) did not show a protective effect against infection (9). The lack of protection from infection in the SIV case might have been due to basing the mosaic design on very limited sampling of a less appropriate population (for a detailed discussion, see Fischer et al (30).…”
mentioning
confidence: 99%
“…In total, we analyzed 10,353 HIV-1 and 17 SIV cpz sequences. Maximum likelihood analysis for group M subtype-specific and SIV cpz consensus sequences revealed relatively low evolutionary diversity for the ISS element with a mean genetic distance of 0.06 Ϯ 0.02 substitution per site in contrast to ϳ0.45 substitution per site (42) reported for the surrounding HIV-1 env region as a whole. Fig.…”
Section: The Iss Element Folds Into a Phylogenetically Conserved Stemmentioning
confidence: 77%